Empreendedorismo bibliotecário no estado do Pará: uma realidade? - MACIEL, Sávio Ricardo Gonçalves (2017)
It examines entrepreneurial initiatives of librarians, besides highlighting characteristics that these professionals must have through the literature available in the area of librarianship, as well as investigate the enterprising initiatives of librarians. The main objective is to investigate the initiatives in the State of Pará. For this purpose, the methodology used was to consult the control bodies about companies in Pará to collect data about the company operating in the region.